PARTISIPASI ISTRI NELAYAN PANDEGA SEBAGAI PENGUPAS RAJUNGAN DALAM UPAYA MENINGKATKAN PENDAPATAN KELUARGA - Ummi Luthfiyatut Tasbichah (Economics Development Analysis Journal, 2015)
Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis (a) kegiatan produktif istri nelayan pandega sebagai pengupas rajungan,(b) besarnya kontribusi pendapatan istri nelayan pandega sebagai pengupas rajungan terhadap total pendapatan keluarganya, (c) kendala-kendala yang dihadapi oleh istri nelayan pandega sebagai pengupas rajungan saat melakukan aktivitas produktifnya. Metode analisis data yang digunakan dalam penelitian ini adalah metode analisis kualitatif dan untuk memperoleh validitas hasil penelitian dilakukan metode triangulasi. Sumber data diperoleh melalui wawancara dengan berbagai pihak yang berhubungan dengan penelitian yaitu istri nelayan pendega sebagai pengupas rajungan kepala kelurahan lokasi penelitian, masyarakat di lokasi penelitian, observasi di lapangan, serta dokumen-dokumen yang berkaitan dengan tujuan dilaksanakannya penelitian. Kontribusi pendapatan informan terhadap pendapatan keluarga cukup besar yaitu 28,19% dari total pendapatan keluarga. Meskipun pendapatan keluarga mengalami peningkatan tetapi peran aktif istri nelayan dalam kegiatan produktif belum mampu mensejahterakan keluarganya. Pekerjaan para istri nelayan di Kelurahan Pacar masih bersifat tradisional belum bisa berkembang yang masih berupa pengupas rajungan biasa tanpa diolah lebih lanjut. Oleh karena itu diharapkan adanya pendampingan program pemberdayaan masyarakat di bidang kelautan dengan cara mengembangkan usaha-usaha mikro produktif seperti pengolahan rajungan yang lebih modern untuk meningkatkan pendapatan istri nelayan pengupas rajungan dan juga diperlukan informasi mengenai pemasaran, keuntungan dan besarnya nilai tambah yang dihasilkan dari perubahan bentuk olahan untuk mengembangkan produksinya. This study aimed to identify and analyze (a) kinds of participation of Pandega’s (fisherman's) wife as a crab peeler in an effort to increase the family income (b) the amount of revenue increase of a Pandega's wife as a crab peeler to the family income, (c) the constraints faced by a Pandega's wife as a crab peeler while doing productive activities. The data analyzed method used in this research is qualitative analyzed methods and to obtain the validity of the results of research conducted triangulation method. Source of data obtained through interviews with various parties related to the wife of research peeler crab fishermen pendega as village chief research sites, communities in research, observations in the field, as well as documents relating to the purpose of the research. The analysis data is used descriptive qualitative analysis method and to obtain the validity of the results of research conducted triangulation method. Source of data obtained through interviews with various parties related to the wife of research peeler crab fishermen pendega as village chief research sites, communities in research, observations in the field, as well as documents relating to the purpose of the research. Informant revenue contribution to the family income is still relatively small, namely 32.16% of the total family income. This indicates that the wife of the income of fishermen small effect on family income as the techniques are still processed manually. Although the family income has increased but the fisherman's wife active role in productive activities have not been able to prosper the family. The work of the wives of fishermen in the village still traditional girlfriend can not evolve is still a regular peeler crab without further processing. Therefore, it is expected the assistance of community development programs in the marine sector by developing micro-enterprises as productive as processing rajungan more modern to improve the income of wives of fishermen peeler crab and also the necessary information regarding marketing, profit and size of the added value resulting from changes in shape processed to developed production.